Mechanical and microstructural characterization of geopolymers derived from red mud and fly ashes. (10th June 2018) - Hu, Wei; Nie, Qingke; Huang, Baoshan; Shu, Xiang; He, Qiang
Abstract: As a toxic industrial waste product, red mud causes severe environmental concern due to its strong alkalinity. In this study, red mud was systematically investigated for beneficial utilization as a raw material for geopolymer production. One type of red mud along with three types of fly ash were utilized to form geopolymers as construction and building materials. Source materials were activated using two types of activator and cured at both ambient and elevated temperatures. The compressive strength, geopolymerization process, and microstructure of the geopolymers were characterized in this study. The geopolymer derived from red mud and class C fly ash obtained a compressive strength of 15.2 MPa under ambient temperature curing at a significantly low NaOH concentration compared to the class F fly ash-based geopolymer. In contrast, the geopolymers derived from red mud and class F fly ash were unable to obtain a serviceable strength when activated with the NaOH solution alone. Elevated temperature curing or using a composite activator proved to be solutions to this issue. This study indicated that the high alkalinity of red mud contributed to geopolymerization, but additional NaOH was necessary to achieve maximum compressive strength.